Analysis of Helios gene expression and Foxp3 TSDR methylation in the newly diagnosed Rheumatoid Arthritis patients. (18th August 2018) - Zafari, Parisa; Yari, Kheirollah; Mostafaei, Shayan; Iranshahi, Nasrin; Assar, Shirin; Fekri, Adel; Taghadosi, Mahdi
ABSTRACT: Background : The control of auto-reactive cells is defective in rheumatoid arthritis (RA). Regulatory T (Treg) cells which play a key role in the modulation of immune responses have an impaired function in RA. Foxp3 is a master regulator of Treg cells which its expression is under the tight control of epigenetic mechanisms. In the current study, we analyzed the epigenetic modulation of the Foxp3 Treg-specific demethylated region (TSDR) and Helios gene expression to determine Treg cells alteration in RA patients. Methods : We have recruited 20 newly diagnosed patients with RA and 41 healthy controls in our study. The measurement of Foxp3 and Helios gene expression was performed by the real-time PCR technique and the methylation level of TSDR was analyzed by bisulfite treatment and quantitative methylation-specific PCR (Q-MSP). Results : We found that RA patients had significantly lower level of Foxp3 gene expression and TSDR demethylation compared to healthy subjects ( P  < 0.001 and P  = 0.006, respectively). Inversely, the Helios gene expression was elevated significantly in RA patients group ( P  = 0.048). We also observed a significant correlation between Foxp3 and Helios gene expression ( P =  0.016) as well as a significant correlation between FoxP3 expression and demethylation rate of TSDR ( P  = 0.010). Conclusion : Our results suggested that both epigenetic modifications and Helios gene expression may have important roles in the pathogenesis of RA through their effects on Foxp3 gene expression.